Neurologic complications of cerebral angiography. - Heiserman, J E; Dean, B L; Hodak, J A; Flom, R A; Bird, C R; Drayer, B P; Fram, E K (American Journal of Neuroradiology, 1994)
PURPOSE To examine the incidence of neurologic complications associated with modern cerebral angiography and to assess patient characteristics associated with an increased risk of complications. METHODS One thousand consecutive cerebral angiographic procedures were evaluated prospectively. Examinations were performed using transfemoral catheterization and film-screen methods. For purposes of this trial, a neurologic complication was defined as any new focal neurologic deficit or change in mental status occurring during the angiogram or within the following 24 hours. Patients were evaluated during and at the completion of angiography. Follow-up evaluations were performed on the day of and the day after angiography. RESULTS There were a total of 10 neurologic complications within 24 hours of angiography, 5 of which were persistent. Onset of 5 of the deficits occurred during angiography, the other 5 (3 persistent) were delayed. All complications occurred in patients being evaluated for stroke/transient ischemic attack or (in one case) asymptomatic bruit. A higher average age, longer average procedure time, and greater volume of radiographic contrast was noted in these patients than in the study population. CONCLUSION Cerebral angiography was associated with a 1% overall incidence of neurologic deficit and a 0.5% incidence of persistent deficit. All complications occurred in patients presenting with a history of stroke/transient ischemic accident or carotid bruit, which may reflect the difficulty of performing angiography in this population at risk for atherosclerotic changes.